From Ideology to Reality: Social Media Addiction Intervention Activity based on DBT Theory - Wang, Shiny; HO CHING ZHUANG; Jin, Shuhe; Yiu (Samuel) Wen (International Journal of Social Sciences and Public Administration, 2024)
This study aims to investigate the effects of teenage social media addition and reasonably intervene. It includes accurate psychological data on 233 teenagers and identifies the Fear Of Missing Out (FOMO) and sense of loneliness in teenagers as influential factors of social media addiction. Based on the sample results, this study used Dialectical Behavior Therapy (DBT) as a basis for addressing this addiction in the form of creative group activities, then setting up surveys to collect feedback on the activity and the method’s effectiveness. Survey results show positive outcomes in improving experiment participants’ mood, social skills and social media reliance after the group activities based on DBT. By organizing and exploring psychological intervention methods through group activities, this research opens a new path within the field of methods towards treating teenage social media addiction.